Can Views and Contact with Nature at Home Help Combat Anxiety and Depression during the Pandemic? Results of the GreenCOVID study. Issue 3 (30th January 2023) - Garrido‐Cumbrera, Marco; González‐Marín, Alicia; Correa‐Fernández, José; Braçe, Olta; Foley, Ronan
Abstract: Background: The COVID‐19 pandemic and the lockdown measures have had important consequences on the mental health of the population, although little is known about the role played by nature and its benefits. Objectives: The present study aims to evaluate the risk of anxiety and depression during the first wave of the COVID‐19 pandemic in Spain and to identify the factors most strongly associated with anxiety and depression, including sociodemographic, household characteristics, and access to or contact with natural environment. Methods: GreenCOVID is an online cross‐sectional study promoted by the Health & Territory Research (HTR) of the University of Seville in Spain, Maynooth University in Ireland, and the University of Winchester in the United Kingdom. This study includes only data from Spain which were collected between April 8, 2020 and April 27, 2020. Binary logistic regression was conducted to identify the factors associated with anxiety and depression through the HADS scale. Results: Of the total of 2, 464 adults who participated in GreenCOVID Spain, mean age was 38.1 years, 72.6% were female, 58.1% were at risk of anxiety, and 32.3% of depression. In the multivariable logistic regression, the factors associated with risk of anxiety were female: gender, being a student and problems at home. Regarding the risk of depression, the factors most associated were being a student, female gender, problems at home, worse evaluation of views from home and less help from outside views to cope with lockdown. Conclusions: Our findings show that during COVID‐19 pandemic, in addition to sociodemographic factors female gender and being a student, problems at home, lack of natural elements in the home, and worse appreciation of views from home were associated with mental health problems. Thus, housing conditions and access to the natural environment were important for mental health during COVID‐19 lockdown. Abstract :